Positive impact of chronic graft‐versus‐host disease on the outcome of patients with de novo myelodysplastic syndrome after allogeneic hematopoietic cell transplantation: a single‐center analysis of 115 patients. (9th November 2013) - Hiramoto, Nobuhiro; Kurosawa, Saiko; Tajima, Kinuko; Okinaka, Keiji; Tada, Kohei; Kobayashi, Yujin; Shinohara, Akihito; Inoue, Yoshitaka; Ueda, Ryosuke; Tanaka, Takashi; Kim, Sung‐Won; Yamashita, Takuya; et al.
Abstract To evaluate the impact of graft‐versus‐host disease (GVHD) and prognostic factors for patients with myelodysplastic syndrome (MDS) after allogeneic hematopoietic cell transplantation (allo‐HCT), we retrospectively reviewed 115 patients with MDS or acute myeloid leukemia with multilineage dysplasia (AML‐MLD) after allo‐HCT at our center. Eighty one patients received reduced‐intensity conditioning (RIC) regimens, whereas 34 received myeloablative conditioning regimens. Although the RIC group was significantly older and included more patients with poor cytogenetic risk, no difference in 4‐yr overall survival (OS) was seen between the two groups. In a multivariate analysis, covariates associated with a worse OS were the French‐American‐British stage of refractory anemia excess blasts in transformation/AML‐MLD at peak, poor cytogenetic risk, bone marrow blasts of 20% or higher at HCT and the absence of chronic GVHD (cGVHD). By using semi‐landmark analyses, we found that the presence of cGVHD significantly improved OS in high‐risk patients or the RIC group. However, there was no difference in OS between those with and without cGVHD among low‐risk MDS patients. These findings suggest that the graft‐versus‐leukemia effect may be more beneficial in high‐risk patients who do not receive intensive preparative regimens.